Micrometric Co3O4/ZIF-67 with high toluene detection capability - Paciencia, Fabiola C. [UNESP]; Theodoro, Reinaldo dos S. [UNESP]; Santos, Gustavo S.M. [UNESP]; Perfecto, Tarcísio M.; Volanti, Diogo P. [UNESP] (Elsevier, 2025)
Environmental monitoring has increasingly focused on detecting volatile organic compounds (VOCs), especially toluene, as these substances pose significant environmental and human health risks. Our research demonstrates the fabrication of microscale Co3O4, a p-type semiconductor material, synthesized through a two-step process combining microwave-assisted hydrothermal synthesis and subsequent calcination. Given the inherent low sensitivity and selectivity of p-type metal oxide semiconductor (MOS) sensors, we explored strategies to enhance the selectivity and sensitivity of p-type MOS under diverse sensing conditions, including varying temperatures and humid environments. The VOC detection performance of Co3O4 was improved by adding a metal-organic framework, ZIF-67. The Co3O4/ZIF-67 composite was prepared using the reflux method. The sensor demonstrated enhanced detection capabilities compared to pure Co3O4, as evidenced by the Co3O4/ZIF-67 composite exhibiting the highest response (61.22) to 100 ppm of toluene at 250 °C, with a high selectivity index (5.43). In contrast, the Co3O4 sensor responded 20.05 to toluene, with a relatively low selectivity index (2.86) at 250 °C. Therefore, the incorporation of ZIF-67 resulted in an enhancement of the sensor's response and selectivity. Furthermore, the sensor demonstrated satisfactory performance at various controlled relative humidities. The micro-sized Co3O4/ZIF-67 demonstrates significant potential as an effective material for low-temperature toluene detection, a crucial capability for monitoring environmental conditions and protecting human health.
Keywords: Cobalt oxide; Gas sensor; p-type semiconductors; Toluene; ZIF-67